The Physical Education labyrinths - Luiz Silva Santos (Journal of Physical Education (Maringá), 2008)
This article aims at describing the way how the protagonists from the Physical Education direct it with the purpose of contributing for the formation of the human being personality. It is based on a qualitative/bibliographic research, having semi-structured interviews as support. Therefore, it was an interpretation of the sense and meaning of the Physical Education teachers social actions who teach at elementary and universitarian courses, including a sample of 58 professors. Through literature and some statements of these interviewers, we could conclude that the relations a lot of teachers have been developing in the ambit of body culture of movement come from the influences that the Physical Education itself has been suffering inside the cultural context. Thus, some conducts related to values, norms and beliefs that can be incorporated to people being submitted to the body culture of movement have been identified. This is true if such teachers are attentive to the circumstantial changes of the society and to the teaching/learning priorities of this knowledge area, what will allow your identity reconstruction, as well as of your students and of the Physical Education itself, as a knowledge field or curricular discipline.